Demonstration of an app-delivered digital therapeutic program for methamphetamine use disorder - Muhlner, Kristin; DeFlavio, Jeff; Ang, Alfonso; Zito, Michael; McLellan, A. Thomas; Perrochet, Brian (Frontiers in Psychiatry, 2023)
This study assessed the feasibility and utility of a digital, all-virtual program designed for treatment of methamphetamine use disorder (MUD). Forty-nine adults with moderate-to severelevel MUD (per DSM-5 criteria) commenced the 8-week intervention. All aspects of the program were delivered via smartphone-based app. Intervention components included counseling (cognitive behavioral therapy in group and individual sessions), app-based therapeutic tasks, remote biological drug testing, medical oversight by psychiatrists/nurse practitioners, and contingency management procedures (including rewards for methamphetamine-free saliva drug tests, accomplishing tasks, and engaging in assigned activities). Of the 49 participants who commenced treatment, 27 participants (55%) completed the program. Repeated-measures mixed-model analyses show that participants were more likely to test negative for meth use from week 1 to week 8 (OR = 1.57, 95% CI [1.28, 1.97]; p = 0.034). Well-being and social functioning improved among the majority of participants. These results demonstrate the utility of the all-virtual, digital therapeutic program and its ability to help individuals with MUD to reduce or cease methamphetamine use. The program was efficiently implemented and was well received by participants and clinical personnel, indicating its ability to deliver comprehensive, effective care and to retain the difficult-to-engage population of persons with MUD. Of the 27 completers, 16 responded to a 1-month follow-up survey and reported no meth use in the month since completing the program.